2007
DOI: 10.1115/1.2719260
|View full text |Cite
|
Sign up to set email alerts
|

Buoyancy-Induced Flow in Open Rotating Cavities

Abstract: Buoyancy-induced flow can occur in the cavity between the co-rotating compressor disks in gas-turbine engines, where the Rayleigh numbers can be in excess of 1012. In most cases the cavity is open at the center, and an axial throughflow of cooling air can interact with the buoyancy-induced flow between the disks. Such flows can be modeled, computationally and experimentally, by a simple rotating cavity with an axial flow of air. This paper describes work conducted as part of ICAS-GT, a major European research … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…For example, Sun et al [35] found considerable difference in heat transfer predictions between LES and URANS. Owen et al [36] showed mixed results from URANS modelling: agreement with disc heat transfer measurements was found for some conditions, but large differences at other conditions. Therefore, this open question is further considered here.…”
Section: Heat Transfermentioning
confidence: 99%
“…For example, Sun et al [35] found considerable difference in heat transfer predictions between LES and URANS. Owen et al [36] showed mixed results from URANS modelling: agreement with disc heat transfer measurements was found for some conditions, but large differences at other conditions. Therefore, this open question is further considered here.…”
Section: Heat Transfermentioning
confidence: 99%
“…For example, Sun et al [36] found considerable difference in heat transfer predictions between LES and URANS. Owen et al [37] showed mixed results from URANS modelling: agreement with disc heat transfer measurements was found for some conditions, but large differences at other conditions. Therefore, this open question is further considered here.…”
Section: Heat Transfermentioning
confidence: 99%
“…However, limitations of the laminar model were recognized. Smout et al (2002), Wong (2002) and Owen et al (2006) have reported the use of conventional k-3 turbulence models in unsteady three-dimensional simulations, but the information available in the open literature is limited. Both Wong's and Owen et al's comparisons with heat transfer measurements gave mixed results.…”
Section: Internal Air System Applicationsmentioning
confidence: 99%